Substrate dependent production and isolation of an extracellular biosurfactant from Saccharomyces cerevisiae 2031. - Alcantara, Virgie A. (Philippine Journal of Science)
Improvements of both biomass yield and emulsification activity are important criteria for profitable biosurfactant production. In this study, Saccharomyces cerevisiae 2031 gave the highest emulsification activity (E24=58 percent) by using Cooper and Paddock's basal medium, containing glucose and waste cooking oil as carbon sources. Glucose and waste cooking oil were found to be essential for high biomass and emulsification activity. Emulsification activity of the biosurfactant increased to 76 percent after optimization of fermentation conditions. The optimum carbon source concentration for both glucose and waste cooking oil was 5 percent. Optimum pH for high biomass production was pH 5.0-8.0. Isolation of the biosurfactant by heat treatment of the S. cerevisiae 2031 cells effectively solubilised the extracellular biosurfactant.